2011
DOI: 10.1007/s00520-011-1249-y
|View full text |Cite
|
Sign up to set email alerts
|

Informational and decisional empowerment in online health support communities: initial psychometric validation of the Cyber Info-Decisional Empowerment Scale (CIDES) and preliminary data from administration of the scale

Abstract: The ability of this composite measure to provide information about the extent to which computer-connected patients view digital peer support as an empowerment tool makes it a valuable addition to the literature in health informatics, supportive cancer care, and health quality of life research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
1
24
0
3
Order By: Relevance
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…All but one of the tools (31) are setting (primary health care (9,32) and hospital care (30) ) or condition-specific. With respect to the condition-specific tools, one addressed mental health (33) , two diabetes (24,29) , two cancer (13,34) , and one clinical genetics (35) . One of the tools (34) addressed two levels of specificity since it assessed cancer patients in virtual spaces.…”
Section: Empowerment Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Ker so SZS pogosto prostor povezovanja posameznikov z občutki in/ali v stanju nemoči (6), jih vrsta avtorjev povezuje s pojmom psihološkega opolnomočenja (7,8). V kontekstu zdravja se psihološko opolnomočenje povezuje zlasti s povečanim občutkom posameznikov, da so se sposobni učinkovito spoprijeti s svojim zdravstvenim stanjem, z boljšimi možnostmi dostopa do zdravstvenih informacij, ustreznejšim nadzorom nad svojimi odločitvami in s komuniciranjem z zdravstvenim osebjem (9)(10)(11)(12). Ugotovljeno je bilo, da vključevanje posameznikov v SZS zanje prinaša pozitivne posledice v smislu individualnega psihološkega opolnomočenja, ki se kažejo kot lažje sprejemanje bolezni, povečanje optimizma in samozavesti pa tudi boljšega splošnega psihosocialnega počutja (9,(13)(14)(15)(16)(17), medtem ko je kolektivni vidik psihološkega opolnomočenja, ki se nanaša na subjektivno oceno možnosti sodelovanja uporabnikov SZS za doseganje pozitivnih učinkov na področju zdravja, sicer poudarjen kot pomemben (17), a hkrati dejansko neraziskan v kontekstu SZS.…”
Section: Uvodunclassified